Efektivitas pemanfaatan Media Audiovisual untuk Meningkatkan Keterampilan Membaca Siswa Kelas V Sekolah Dasar : Literatur Review - Mutiara Adesa Madani; Melva Zainil (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Reading is a basic language skill that plays a crucial role in the learning process at the elementary level. However, many students in grade V of elementary schools still face difficulties in reading comprehension. This study aims to analyze the effectiveness of audiovisual media in improving reading skills of fifth grade students. The research method used is Systematic Literature Review (SLR), by analyzing various national journals and studies published within the last five years. The results of the literature review indicate that audiovisual media significantly enhances students' interest, focus, and comprehension in reading activities. In conclusion, audiovisual media is proven to be a practical and innovative tool to support reading instruction, and its implementation is recommended to improve literacy outcomes in elementary education.